2005
DOI: 10.1080/02841860500326000
|View full text |Cite
|
Sign up to set email alerts
|

Living after radical prostatectomy for localized prostate cancer. A qualitative analysis of patient narratives

Abstract: The purpose of this study was to illuminate the experience of living after radical prostatectomy (RP) for localized prostate cancer (LPC). Ten men were interviewed after RP. The interview text was qualitatively analyzed using the content analysis. The men suffered from worry, anxiety, and distress, and longed for life as they had lived it before the diagnosis. Changes in bodily functions after RP include urine incontinence (UI) and/or erectile dysfunction (ED) making the patient feel like a changed man with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(154 citation statements)
references
References 26 publications
10
142
0
2
Order By: Relevance
“…In Sanda's study, partners also report being bothered with regard to men's sexual changes. Wei's and Sanda's results are supported by Hedestig, 33 Bokhour, 34 Katz 35 and colleagues, who show that men feel demoralized and emasculated by loss of sexual functioning after prostate cancer treatment. If, as suggested by Moinpour et al, after 5 years, men report an overall high-health QOL, we may assume that they have found a way to cope with the loss of erection.…”
supporting
confidence: 72%
“…In Sanda's study, partners also report being bothered with regard to men's sexual changes. Wei's and Sanda's results are supported by Hedestig, 33 Bokhour, 34 Katz 35 and colleagues, who show that men feel demoralized and emasculated by loss of sexual functioning after prostate cancer treatment. If, as suggested by Moinpour et al, after 5 years, men report an overall high-health QOL, we may assume that they have found a way to cope with the loss of erection.…”
supporting
confidence: 72%
“…36,39 Several qualitative studies described patient reports of loss of manhood and loss of familiar self that can come with the sexual side effects of prostate Sexual recovery after prostate cancer D Wittmann et al cancer treatment. 35,40 Men also experienced loss of the capacity to respond to sexual cues, sexual fantasies, and spoke with nostalgia about past sexuality and loss of self-worth. Some men avoided sexual encounters for fear of failure or embarrassment.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies have provided some insight into the experiences of living with prostate cancer. For instance, Hedestig et al [14] conducted interviews with patient with untreated LPCa and analysed the interview transcripts using in-depth qualitative narrative analysis. Their findings revealed that men perceived their disease as life-threatening, experienced uncertainty, fear and worry about their cancer progression, and a repressed sense of manhood due to sexual dysfunctions.…”
Section: Treatment Side-effects and Their Psychological Impactmentioning
confidence: 99%